THE INFLUENCE OF THE INQUIRY LEARNING MODEL ON THE LEARNING OUTCOMES OF NATURAL SCIENCES CLASS FOUR ELEMENTARY SCHOOL - Rizky Ajeng Ayuningtias; Diki Rukmana (Universitas Majalengka, 2023)
The learning process can influence a student’s success in achieving educational goals. However, the lack of innovation in elementary school natural science learning models makes it difficult for students to assimilate the presented material. This research aims to determine the influence of the guided inquiry learning model on the learning outcome of Natural Sciences. Research methods use quantitative research methods, quasi-models experiment with a pretest-posttes-only control design pattern, and the type of instrument use using a double choice test using 2 class samples on the experimental class using. The inquiry model is guided, and the control class uses the conventional learning outcomes of students in the fourth grade of the Master of Science. This is a supported by a cognitive hypothesis test with the results of N_sig < N_table with a score of 0.015 < 0.05. test affective hypothesis test with the results of N_sig < N_table with a score of 0.000 < 0.05, and psychomotor hypothesis test, whit the results of N_sig < N_table, with score of 0.000 < 0.005. based on the research, It can be concluded that the guided inquiry learning model influence the results of natural science learning in the fourth grade of elementary. Proses pembelajaran dapat mempengaruhi keberhasilan siswa untuk mencapai tujuan pendidikan. Namun kurangnya inovasi model pembelajaran pada pelajaran ilmu pengetahuan alam di sekolah dasar membuat siswa mengalami kesulitan untuk memahami materi yang diajarkan. Penelitian ini bertujuan melihat pengaruh model pembelajaran inkuiri terbimbing terhadap hasil belajar ilmu pengetahuan alam kelas IV SD, metode yang digunakan adalah kuasi eksperimen dengan pretest-posttest-only control desain. Sempel yang dipakai adalah sebanyak 2 kelas dipilih secara random sampling, kelas eksperiment sebanyak 30 siswa dan kontrol sebanyak 30 siswa. Hasil penelitian ini menunjukan bahwa model pembelajaran yang dipandu oleh survei mempengaruhi hasil belajar ilmu alam pengetahuan alam kelas IV di sekolah dasar. Hasil ini didukung oleh tes hipotesis dengan hasil hipotesis kognitif N_sig < N_table dengan nilai 0.015 < 0.05., hipotesis afektif dengan nilai 0.000 < 0.05 dan hipotesis psikomotor dengan nilai 0.000 < 0.05. Hasil penelitian yang diperoleh dapat disimpulkan bahwa model pembelajaran tersebut memiliki pengaruh yang dipandu pada hasil belajar ilmu pengetahuan alam kelas IV di sekolah dasar.